Proceedings of the 12th ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming 2007
DOI: 10.1145/1229428.1229437
|View full text |Cite
|
Sign up to set email alerts
|

On using connection-oriented vs. connection-less transport for performance and scalability of collective and one-sided operations

Abstract: Communication subsystem plays a pivotal role in achieving scalable performance in clusters. The communication semantics employed are dictated by the programming model used by the application such as MPI, UPC, etc. Out of the gamut of communication primitives, collective and one-sided operations are especially significant and have to be designed harnessing the capabilities and features exposed by the underlying networks. In some cases, there is a direct match between the semantics of the operations and the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Researchers have previously shown the benefit of using hardware-based multicast over UD to increase collective performance in MVAPICH [18,20]. Mamidala, et al, has also shown the benefit of using UD for MPI Alltoall operations [21]. Our work instead focuses on a complete MPI stack over UD for high-performance and scalable point-to-point performance.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have previously shown the benefit of using hardware-based multicast over UD to increase collective performance in MVAPICH [18,20]. Mamidala, et al, has also shown the benefit of using UD for MPI Alltoall operations [21]. Our work instead focuses on a complete MPI stack over UD for high-performance and scalable point-to-point performance.…”
Section: Related Workmentioning
confidence: 99%